2017
DOI: 10.3389/fnhum.2017.00518
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Analysis of Neural Mechanisms Underlying the Maturation of Multisensory Speech Integration in Neurotypical Children and Those on the Autism Spectrum

Abstract: Failure to appropriately develop multisensory integration (MSI) of audiovisual speech may affect a child's ability to attain optimal communication. Studies have shown protracted development of MSI into late-childhood and identified deficits in MSI in children with an autism spectrum disorder (ASD). Currently, the neural basis of acquisition of this ability is not well understood. Here, we developed a computational model informed by neurophysiology to analyze possible mechanisms underlying MSI maturation, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 102 publications
(171 reference statements)
1
26
0
Order By: Relevance
“…Our data suggest that the amelioration of multisensory deficits in ASD generalizes to the case of nonsocial AV stimuli, but that the developmental trajectory of this recovery is protracted compared to that observed in AV speech studies (e.g., Taylor et al, 2010;Foxe et al, 2015). We hypothesized that this delay may be due to lack of environmental exposure to such ecologically-rare stimuli (Beker et al, 2017;Cuppini et al, 2017), and/or engagement of neural processes with longer developmental trajectories. Indeed, multisensory gain in NT individuals has been shown to reach full maturity much later for simple AV stimuli, such as those used here (Brandwein et al, 2011), compared to AV speech stimuli (Ross et al, 2011).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our data suggest that the amelioration of multisensory deficits in ASD generalizes to the case of nonsocial AV stimuli, but that the developmental trajectory of this recovery is protracted compared to that observed in AV speech studies (e.g., Taylor et al, 2010;Foxe et al, 2015). We hypothesized that this delay may be due to lack of environmental exposure to such ecologically-rare stimuli (Beker et al, 2017;Cuppini et al, 2017), and/or engagement of neural processes with longer developmental trajectories. Indeed, multisensory gain in NT individuals has been shown to reach full maturity much later for simple AV stimuli, such as those used here (Brandwein et al, 2011), compared to AV speech stimuli (Ross et al, 2011).…”
Section: Discussionmentioning
confidence: 83%
“…computational (Cuppini et al, 2017) perspectives have suggested that the constant exposure to AV speech during maturation may serve to train multisensory speech function, leading to earlier developmental recovery of function in ASD. Furthermore, the underlying neural processes that are engaged in different contexts may follow disparate developmental trajectories; the trajectory of multisensory development in NT individuals reaches full maturity much earlier for speech stimuli (Ross et al, 2011) compared to nonspeech stimuli (Brandwein et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we tested the abilities of children with a hyper-responsive SPD phenotype to recognize speech inputs under varying levels of background noise using a well-established assay of multisensory speech integration. It is clear from decades of work that neurotypical individuals gain substantial benefits in speech comprehension from both seeing and hearing a speaker under such circumstances (Sumby and Pollack, 1954 ; Erber, 1969 ), so assays of multisensory speech integration have become one of the primary means by which multisensory processing abilities are measured in various clinical and neurotypical groups (Smith and Bennetto, 2007 ; Irwin et al, 2011 ; Hahn et al, 2014 ; Foxe et al, 2015 ; Cuppini et al, 2017 ; Beker et al, 2018 ). The current results reveal a significant deficit in the abilities of children with an SPD to benefit from multisensory speech inputs, relative to a cohort of matched typically developing control participants.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the wealth of evidence highlighting disturbances across a number of sensory systems in ASD, there has been keen interest in studying the integration of information across these different sensory modalities [Beker, Foxe, & Molholm, 2018; Cuppini et al, 2017; Feldman et al, 2018]. Such multisensory integration is fundamental in allowing us to successfully interpret communicative and social signals.…”
Section: Atypical Multisensory Processing In Autism Spectrum Disordermentioning
confidence: 99%
“…Evidence of decreased multisensory gain or benefit has been reported utilizing both simple and complex stimuli [Collignon et al, 2013; Mongillo et al, 2008; Stevenson et al, 2014; Stevenson et al, 2014]. Further, these multisensory deficits have been correlated with symptom severity [Brandwein et al, 2015; Yaguchi & Hidaka, 2018], and the development of multisensory function and its neural underpinnings may be atypical in ASD as well [Beker et al, 2018; Brandwein et al, 2012; Cuppini et al, 2017; Foxe et al, 2015; Stevenson et al, 2013; Taylor, Isaac, & Milne, 2010].…”
Section: Atypical Multisensory Processing In Autism Spectrum Disordermentioning
confidence: 99%